The Distribution and Function of Aquaporin 1 and 2 Along the Kidney in Different Species - An,Fengli (Sociedad Chilena de Anatomía, 2021)
SUMMARY: Water metabolism in kidney is critical for organisms living in arid environments. In this study, the kidney structure and the expression of AQP1 and AQP2 in Phrynocephalus vlangalii and Camelus bactrianus were studied. It was found that the Phrynocephalus vlangalii has fewer renal corpuscle but developed kidney tubules, and AQP1 and AQP2 were mainly expressed in the kidney tubules. Camelus bactrianus has a large diameter of glomerulus, thick bulbar membrane, and long and dense urinary tract. AQP1 was highly expressed in the proximal convoluted tubule, proximal straight tubule, and Ansa nephroni (Henle´s loop), and AQP2 was also highly expressed in the collecting tubule and distal convoluted tubule. In the long-term evolutionary adaptation, the morphological structure of animal kidney is consistent with its environment. In addition to structural and functional adaptation, aquaporin also participates in the adaptation to water scarcity environment, and may also play a key role.